Design of Conveyor System Based on Microcontroller - Wulandari, Rindi (AI Society & STMIK Indonesia, 2023)
Conveyor is a transport system that can move objects from one point to another. This study aims to make a conveyor system based on mikrokontroller by testing several materials for the conveyor base, and testing the performance of the conveyor system. The microcontroller used is Arduino Uno. The sensor used is an infrared sensor, as a sensor for detecting objects on the conveyor. The research method used is an applied research method with experimental techniques. The first stage is to create a mechanical design for the conveyor, and the second is make an automation design. The results of the study show that the most effective material for the conveyor belt base is a 1.5 cm thick mattress material. The system test results show that the infrared sensor can be used to detect objects on the conveyor. When an object is detected, the conveyor stops for 0.5 seconds and is detected on the LCD monitor in the control box. The range of the infrared sensor is 15 cm – 50cm.